Integrasi Islam Dalam Struktur Pemerintahan Dan Kehidupan Sosial Kedatuan Suppa Di Ajatappareng Abad 17 Masehi - Abdul Azis; Nurul Ummisa; Muh. Ardiansyah (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The process of Islamization in the Kedatuan Suppa in the 17 century AD took place through various channels, not only influenced by trading activities and the arrival of preachers from outside, but also by the central role of the palace, especially Datu We Passulle Daeng Bulaeng. This research aims to examine how Islam was integrated into the governmental structure and the social life of the Suppa community at that time. By using the historical method which consists of heuristics, criticism, interpretation, as well as historiography and an anthropological-sociological approach, this research studies the role of the palace in institutionalizing Islam through the establishment of Parewa Syara’ as well as the alignment of Bugis customs with the values of sharia. The results of the research show that Islam did not completely replace customs, but rather carried out a process of acculturation with local values that were in accordance with the principle of tawhid. This transformation is evident in governance, religious practices, and life rituals such as birth, marriage, and death. Overall, Islam appeared as a normative and cultural force that strengthened the socio-political order of the Kedatuan Suppa in an adaptive and transformative manner.